A230 NOT ALL PATIENTS WITH GASTROINTESTINAL COMPLAINTS REQUIRE SPECIALIST CARE: TWO YEAR OUTCOMES FROM AN ENHANCED PRIMARY CARE PATHWAY. (1st March 2018) - Mazurek, M S; Belletrutti, P J; Halasz, J; Heather, G S; Swain, M; Novak, K L
Abstract: Background: High referral volumes to digestive disease specialists in Canada highlight the ubiquity of gastrointestinal disorders. Yet, due to demand-supply mismatch, wait times for specialist consultation continue to grow, exceeding consensus targets. At our institution, a single point of entry model is used to centralize intake. Recently, an Enhanced Primary Care (EPC) pathway was created to identify certain low-risk patients who do not require immediate specialist consultation. These patients are managed by their primary care physician with support from co-developed best practice guidelines. Aims: This study aims to evaluate the overall safety and outcomes for patients declined by our central triage referral system. Methods: All patients triaged to the EPC pathway from January 1, 2015–January 31, 2017 were identified. The subset that re-entered the system through an emergency room (ER) visit and/or re-referral to a specialist was determined. Anonymized patient data, including demographics, referral indication, and referral closure date were abstracted and correlated with endoscopic and histopathologic findings. Clinically significant findings were defined as those imparting significant morbidity or need for further specialist management. Results: During the 25-month study period, a total of 1266 unique closed referrals were captured. 136 patients (10.7%) had a subsequent gastrointestinal-related ER visit, of which, 45 (33%) went on to endoscopy. Overall, 192 patients (15.2%) re-entered the referral system and had assessment with esophagogastroduodenoscopy (67%), colonoscopy (17%), sigmoidoscopy (2%), or bidirectional endoscopy (14%). The median time from referral closure to endoscopy was 186 days (range 6–804). The majority of patients were female (60.9%) with an overall median age of 43 years (range 18–87). The most common indications for re-referral were dyspepsia (42%), gastroesophageal reflux (28%), and suspected irritable bowel syndrome (20%). Overall, clinically significant findings were identified in only 4 of 214 procedures (2%). These included 2 patients with esophagitis, 1 advanced adenoma, and 1 benign peptic stricture. No patients were found have malignancy, inflammatory bowel disease, microscopic colitis, or celiac disease. Fully 148 of 214 procedures (69%) were completely normal. Conclusions: Not all patients referred for gastrointestinal consultation require specialist care or endoscopy. Through careful patient selection, the use of the EPC pathway is both safe and effective in identifying low risk patients who are most appropriately managed within primary care. This facilitates optimization of consultative and endoscopic resources for higher risk patients. Funding Agencies: Division of Gastroenterology, University of Calgary